Human Resource Competence and Work Motivation on Perfomance Employee - Sabil Sabil; Aprih Santoso; Sylvia Kartika Dhamayanti; Ratnawati Ratnawati; Ridwan Ridwan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Employee performance is influenced by HR expertise. Good employee performance is attained because people are highly motivated at work and possess HR competency. Field study with a quantitative approach is the research methodology employed. There were 99 employees of BNI Syariah Semarang City that made up the study's population. A questionnaire is used in the data collection process. Employee Performance (Y1) is positively influenced by the two research variables, Human Resources Competence (X1) and Work Motivation (X2), as indicated by their positive regression coefficients. Consequently, an increase in either of these variables will result in an increase in Employee Performance (Y1). The variables of Work Motivation and Human Resources Competence have a computed F value of 42.523 at the significance level of 0.000. Given that the calculated F value is 42.523 > F table 3.94 and the significance value is (Sig.) 0.000 < 0.05 with a positive sign, it may be concluded that Ha is accepted and H0 is rejected. The results of the multiple linear regression analysis of the coefficient of determination showed a R² (Adjusted R Square) value of 0.459, meaning that the independent variables of work motivation and human resources competence had a 45.9% influence on employee performance, with the remaining portion being influenced by factors that have not yet been investigated.